Investigation of composition, antioxidant, antimicrobial and cytotoxic characteristics from Juniperus sabina and Ferula communis extracts - Doga Kavaz; Razan El Khaled El Faraj (Scientific Reports, 2023)
Abstract Plants have been one the most valuable sources of biologically active compounds. This study investigates the chemical composition, as well as the antioxidant, antimicrobial, and cytotoxic activities of methanolic and ethanolic extracts from Juniperus sabina and Ferula communis leaves, grown in Cyprus. Total phenolic and flavonoids content of methanol and ethanol extracts were quantified. Chemical constituents of the leaf extracts were analysed using gas chromatography/mass spectrometry (GC/MS). Mome inositol was the predominant component in the J. Sabina’s extracts. The most dominant component in F. communis ethanolic extract was phytol, while in FCL methanolic extract 1,3,4,5 tetrahydroxycyclohexanecarboxylic acid. Antioxidant activities were evaluated by 1, 1-diphenyl-2-picrylhydrazyl (DPPH) free radical-scavenging ability. Antioxidant activity results revealed concentration dependent activity for methanolic and ethanolic extracts from the plant leaves. Antibacterial activity of plant extracts was tested against Gram-negative and Gram-positive bacteria using disk diffusion and minimal inhibitory concentration methods. Cytotoxic activity of plant extracts were evaluated on MCF-7 and MDA-MB-231 breast cancer cell lines, where they demonstrated their potential on the viability of both cell lines. The biological activity revealed by plants is due to the bioactive compounds found in the extracts. These bioactive components could be used as anticancer drug candidates.